Hydrogen-bonded networks based on [M(H2biim)3]2+ anion receptors with chiral recognition guests [M(H2biim)2phen]2+ (H2biim = 2, 2′-biimidazole, phen = 1, 10-phenanthroline). (8th January 2015) - Yang, Yong-Sheng; Yang, Yu-Ping; Liu, Min; Qiu, Qi-Ming; Jin, Qiong-Hua; Sun, Jing-Jing; Chen, Hua; Dai, Yong-Cheng; Meng, Qing-Xuan
Abstract : Graphical abstract: Three isostructure complexes [M(H2 biim)3 ][M(H2 biim)2 (phen)](NO3 )4 (M = Co, Ni, Zn) with diverse hydrogen bonding modes between the nitrate and H2 biim ligand were synthesized. Each Δ (or Λ)-[M(H2 biim)2 (phen)] 2+ unit as the guest recognizes Δ (or Λ)-[M(H2 biim)3 ] 2+ through these hydrogen bonding modes. Abstract: Reactions of transition metal(II) nitrate with 2, 2′-biimidazole and 1, 10-phenanthroline generated three new isostructural complexes, [Co(H2 biim)3 ][Co(H2 biim)2 (phen)](NO3 )4 ·2CH3 OH·H2 O (1 ), [Ni(H2 biim)3 ][Ni(H2 biim)2 (phen)](NO3 )4 ·3.5H2 O (2 ), and [Zn(H2 biim)3 ][Zn(H2 biim)2 (phen)](NO3 )4 ·4H2 O (3 ) (H2 biim = 2, 2′-biimidazole, phen = 1, 10-phenanthroline). These complexes were characterized by single-crystal X-ray diffraction, elemental analysis, luminescent spectra and thermogravimetric analysis. The crystal packing of the complexes show that cationic [M(H2 biim)3 ] 2+ fragments are self-assembled to construct the 2-D supramolecular networks by hydrogen bonding and π–π interactions. The guest molecule [M(H2 biim)2 phen] 2+ is well recognized by the N–H⋯O and O–H⋯O hydrogen bonds. In complexes1 –3, chiral guest molecules recognize the chirality of the host cations [M(H2 biim)3 ] 2+, which are assembled into 2-D nets with alternating Δ and Λ chirality resulting in the structure of racemates. The data observed in this paper suggest that the diverse hydrogen bonding modes between the nitrate and H2 biim ligand identified here play a crucial role in the formation of1 –3 .